Perceived social-emotional competence: A multidimensional examination and links with social-emotional motivation and behaviors. (December 2022) - Collie, Rebecca J.
Abstract: This study examined perceived social-emotional competence (perceived-SEC) and its links with students' social-emotional motivation (i.e., autonomous and controlled motivation) and behavior (parent-reported prosocial behavior and conduct problems). Five types of perceived-SEC were examined: perceived competence for assertiveness, tolerance, social regulation, emotion regulation, and emotional awareness. With data from 414 Australian students, structural equation modeling demonstrated that an overarching (global) perceived-SEC factor was positively associated with autonomous motivation, introjected regulation, and prosocial behavior, and negatively associated with conduct problems. Two specific dimensions also had unique associations with the behaviors: Perceived competence for social regulation was negatively associated with external motivation and conduct problems, and perceived competence for tolerance was positively associated with autonomous motivation. In turn, autonomous motivation was positively associated with prosocial behavior, whereas external motivation was positively associated with conduct problems. Findings hold relevance for efforts aiming to understand the role of motivational drivers of students' social-emotional competence. Highlights: Five types of perceived social-emotional competence (perceived-SEC) were examined. A global factor and five specific factors of perceived-SEC were identified. The perceived-SEC factors were linked with social-emotional motivation. Perceived-SEC and social-emotional motivation were linked with prosocial behavior. The predictors were also associated with conduct problems.